Eco-Printing Technique of Mimosa Tanned Sheepskin at Different Temperatures on Fastness and SEM of Tanned Leather - Nirmalawati, Elisa; Pertiwiningrum, Ambar; Abidin , Mohammad Zainal (Faculty of Animal Science Universitas Brawijaya, 2025)
This study aimed to evaluate the quality of sheepskin after the tanning process using mimosa and to analyze the microscopic structure of mimosa-tanned sheepskin that had been eco-printed. The research method used sheepskin samples that had undergone optimal with mimosa. The sheepskin tanning research evaluated samples subject to four different treatments: treatment A (15% mimosa), treatment B (20% mimosa), treatment C (25% mimosa), and treatment D (30% mimosa). The sheepskin eco-print research compared the sheepskin eco-print samples treated with treatment 1 (temperature 60oC), and treatment 2 (temperature 65oC). The evaluation of tanned leather quality was conducted by measuring several parameters, such as tensile strength, elongation, tear strength, thickness, plasticity, and shrinkage temperature. The quality of the sheepskin eco-print was evaluated by measuring the color fastness to rubbing, and SEM (Scanning Electron Microscopic). The data obtained were analyzed statistically using variance analysis of a complete randomized design with a unidirectional pattern. In instances where significant differences were identified, a mean difference test was performed with Duncan's Multiple Range Test. The results showed that tanning leather using mimosa, conducted in stages had a significant effect (p < 0.05) on the parameters of tensile strength, extensibility, tear strength, thickness, goldenness, and shrinkage temperature. The application of tanner with 30% mimosa on sheepskin emerged as the best tanner concentration. The treatment resulted in a tensile strength value of 1332.28 N/cm2, elongation of 45.90%, tear strength of 102.9 N/cm, thickness of 2.06 mm, plasticity of 5.33 mm, and shrinkage temperature of 81.73oC. Additionally, the results of the color fastness test against wet and dry rubbing, along with SEM from the 60oC produced good eco-print results.